Analisis Faktor Keterlambatan Pekerjaan Konstruksi Drainase dengan Menggunakan Metode Kaiser Mayer Oklin (KMO) - Nugraha, Trinata Budi; Rodhi, Nova Nevila; Sari, Ayu Kurnia Ratna (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to identify factors that cause delays in implementing the Urban Drainage project in Kepatihan Village, Bojonegoro Regency, using Regional Revenue and Expenditure Budget (APBD) funds. The research method used a population involved in drainage construction, using a saturated sampling technique with 39 respondents. Data collection used questionnaires for primary data and secondary data obtained from project schedules, cost budget plans and workforce data. Data analysis uses factor analysis, descriptive analysis, and cross tabulation analysis. Factor analysis uses the Kaiser Mayer Olkin Measure of Sampling Adequacy (KMO-MSA) method. The KMO test was carried out with a significance value from the Bartlett Sphericity Test of less than 0.05 to determine the suitability of the variables. The KMO-MSA process is carried out by calculating the Kaiser Mayer Olkin (KMO) value. The KMO value ranges between 0 and 1, where a higher value indicates a better match. Apart from that, Bartlett's Test of Sphericity was also carried out to test the significance of the relationship between variables. If the test results are significant (p < 0.05), then these variables are suitable for proceeding to further factor analysis. The results of the cross-tabulation analysis show that the labor variable (X2) is the main factor influencing delays in drainage construction projects, with a significance value (sig) < 0.05. Based on the results of the descriptive analysis, the labor factor indicator (X2) which is the factor that has the most significant influence on construction project delays, is the variable X2.1 in the form of labor availability with a mean of 5.67 and a percentage value of 5.12%. This suggests that a lack of labor can cause delays in project implementation, potentially affecting overall project progress and quality.